2011
DOI: 10.1108/20442081111180368
|View full text |Cite
|
Sign up to set email alerts
|

Music festival sponsorship: between commerce and carnival

Abstract: Purpose -This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid-1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach -The paper uses extant research materials to construct an account of British music festival history since the mid-1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 12 publications
1
50
0
2
Order By: Relevance
“…Music festivals are a worthwhile area of study because research has found they are places to foster social change (Anderton, 2011;Cummings, 2008;Sharpe, 2008) and provide positive impacts on participants' psychological and social well-being (Adsett, 2011;Ballantyne et al, 2014;Gursoy et al, 2004;Packer & Ballantyne, 2010). This impact is the result of the unique opportunities that music festivals provide for interaction between attendees and music in an active way, allowing attendees to be open to experiences that lead to personal growth and self-discovery.…”
Section: Music Festival Events As the Context Of This Researchmentioning
confidence: 99%
“…Music festivals are a worthwhile area of study because research has found they are places to foster social change (Anderton, 2011;Cummings, 2008;Sharpe, 2008) and provide positive impacts on participants' psychological and social well-being (Adsett, 2011;Ballantyne et al, 2014;Gursoy et al, 2004;Packer & Ballantyne, 2010). This impact is the result of the unique opportunities that music festivals provide for interaction between attendees and music in an active way, allowing attendees to be open to experiences that lead to personal growth and self-discovery.…”
Section: Music Festival Events As the Context Of This Researchmentioning
confidence: 99%
“…Greater professionalisation (Anderton, 2011) is not only the domain of private and public sector events as 'a "grassroots" event does not preclude the adoption of a formal or professional approach' (Richards & Ryan, 2004, p. 96). A professionalised approach began in Stage 2 when the BFF gained charitable status and experience in managing regulatory pressures.…”
Section: Stage 3: Maturationmentioning
confidence: 99%
“…Carnival signalled a temporary suspension of regulatory forces and an opportunity for participants to transgress societal conventions (Bakhtin, 1984a(Bakhtin, , 1984b). Bakhtin's (1984aBakhtin's ( , 1984b concepts have been applied to, for example, events (Anderton, 2008(Anderton, , 2011Harcup, 2000;Islam, Zyphur, & Boje, 2008;Kates & Belk, 2001;Ravenscroft & Matteucci, 2003), music and dance cultures (Hanlon, 2004;Presdee, 2000;Vitos, 2010) and these existing studies often concentrate on the following. First, contemporary studies have applied Bakhtin's (1984aBakhtin's ( , 1984b theorisation to events and identified those features corresponding to the carnivalesque (Gilmore, 1995;Kates, 2003;Kates & Belk, 2001;Ravenscroft & Matteucci, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point was also emphasized by both Frost and Laing (2013) and Sharpe (2008)-even those already engaging in the desired behavior need support and reinforcement of their lifestyle choices, and events may help support, pride, and equality; and the Burning Man Festival in Nevada, which promotes radical art and free expression (Frost & Laing, 2013). Further, many events are associated with counterculture, and have a strong history of promoting social justice (Anderton, 2011). The Glastonbury Festival is just one example of such an event, but there are many around the world.…”
Section: Literature Reviewmentioning
confidence: 99%